A little princess - Burnett, Frances Hodgson, 1849-1924 (Boston, Mass : Thomson Heinle, 2007)
Sara Crewe, a pupil at Miss Michin's London School, is left in poverty when her father dies, but is later rescued by a mysterious benefactor
Keywords: Boarding schools -- Fiction; Schools -- Fiction; Orphans -- Fiction